O profissional arquivista e a gestão documental como mecanismo de apoio para o acesso à informação, transparência pública e exercício da democracia. - Rabelo, Sara Diane Silva (Brasil, 2022)
The present work aims to analyze the theme about the professional archivist and Document Management as support mechanisms for access to information and Public Transparency and the exercise of democracy with the objective of reporting the historical and theoretical aspects of the professional archivist, as well as the importance of their acting in public organizations; identify the challenges in relation to the lack of Document Management in public organizations; to describe the main problems of the daily life of public organizations in relation to Document Management. The purpose of this study is to analyze through bibliographic research, documentary research the importance of document management and how much it directly implies public transparency and the exercise of democracy when applied within an institution and to report the need of the archivist professional for companies whose documents archives need management, making improvements in public transparency, giving society access to information, with the appropriate treatment. The descriptive theoretical method was used, bringing speeches from authors who report on document management and public transparency.